과민성 장 증후군에서 소장세균과다증식의 예측을 위한 락툴로오스 호기검사의 유용성 - 박정수; Jung Soo Park; 유정환; Jung Hwan Yu; 임현철; Hyun Chul Lim; 김지현; Jie Hyun Kim; 윤영훈; Young Hoon Yoon; 박효진; Hyo Jin Park; et al. (The Korean journal of gastroenterology, 2010)
목적: 소장세균과다증식(SIBO)은 과민성 장 증후군(IBS) 병태생리의 하나로 간주되며, 진단방법으로 락툴로오스 호기검사(LBT)가 사용되고 있으나, 유용성에는 논란이 있다. 이번 연구는 IBS와 기능성 장질환(FBD) 환자에서 락툴로오스 호기검사를 분석하여 유용성을 분석하고자 한다. 대상 및 방법: 로마기준 III의 IBS 환자 76명, FBD 환자 70명, 건강한 성인 40명을 대상으로 하였다. LBT를 시행하여 호기 수소 및 메탄가스 농도를 측정하였고, 수소 생산군(PHP)과 메탄 생산군(PMP)으로 구분하였다. 또한, IBS군에서 변비/설사 우세형, 혼합형의 아형으로 구분하여 분석하였다. 결과: LBT 양성률은 IBS군 44.7%, FBD군 41.4%, 대조군 40.0%로 의미있는 차이는 없었다. PHP는 각각 11.8%, 22.9%, 7.5%이며, PMP는 25.0%, 15.7%, 25.0%로 각 군 사이에 차이는 없었다. IBS, FBD 환자군을 LBT 양성군과 음성군으로 분류하여 비교하였을 때, 양 군 간의 나이, 성별, 증상에 유의한 차이가 없었다. 특히, IBS 환자군의 경우 IBS의 아형에 유의한 차이가 없었다. IBS군을 수소 생산군, 메탄 생산군, 혼합 생산군, 가스 비생산군으로 분류하였을 때 LBT 가스 생성패턴에 따른 나이, 성별, IBS의 아형 및 증상에 유의한 차이는 없었다. 결론: LBT는 IBS와 FBD군, 대조군 사이의 임상적 차이를 대변하지 못하였다. IBS에서 SIBO를 예측함에 있어 호기검사의 유용성은 재평가가 필요할 수 있다. Background/Aims: Lactulose breath test (LBT) has been `used as a presumptive surrogate marker for small intestinal bacterial overgrowth (SIBO). However, recent reports suggest that abnormal LBT cannot discriminate patients with irritable bowel syndrome (IBS) from the control. Thus, the aim of this study was to evaluate the usefulness of LBT in IBS. Methods: LBT from 76 IBS patients, 70 functional bowel disorders (FBD), and 40 controls were examined. LBT was considered positive if (1) baseline breath hydrogen (H2) ＞20 parts per million (ppm) or rise of breath H2 ＞20 ppm above the baseline in ＜90 mins, or (2) baseline breath methane (CH4) ＞ 10 ppm or rise of breath CH4 ＞10 ppm above the baseline in ＜90 mins. The subjects were categorized into predominant hydrogen producers (PHP), predominant methane producers (PMP), combined producer, and both negative group based on LBT. Results: The rate of abnormal LBT in the IBS, FBD, and control group were 44.7%, 41.4%, and 40.0% respectively without significant differences. The rate of PHP or PMP was not significantly different among the IBS, FBD, and control group. When clinical characteristics were analyzed in IBS and FBD according to LBT types, IBS subtypes and symptoms were not significantly different. Conclusions: LBT was not useful to discriminate IBS/FBD patients from the control. The assessment of SIBO by LBT in IBS should be revalidated in the future. (Korean J Gastroenterol 2010;56:242-248)